2015 IEEE International Conference on Communications (ICC) 2015
DOI: 10.1109/icc.2015.7248815
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient offloading for competing users on a shared communication channel

Abstract: In this thesis we consider a set of mobile users that employ cloud-based computation offloading. In computation offloading, user energy consumption can be decreased by uploading and executing jobs on a remote server, rather than processing the jobs locally. In order to execute jobs in the cloud however, the user uploads must occur over a base station channel which is shared by all of the uploading users. Since the job completion times are subject to hard deadline constraints, this restricts the feasible set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…A few recent works provided a game theoretic treatment of computation offloading in a game theoretical setting [24], [25], [7], [26], [27], [28]. [24] considers a two-stage problem, where first each mobile user decides what share of its task to offload so as to minimize its energy consumption and to meet its delay deadline, and then the cloud allocates computational resources to the offloaded tasks.…”
Section: Related Workmentioning
confidence: 99%
“…A few recent works provided a game theoretic treatment of computation offloading in a game theoretical setting [24], [25], [7], [26], [27], [28]. [24] considers a two-stage problem, where first each mobile user decides what share of its task to offload so as to minimize its energy consumption and to meet its delay deadline, and then the cloud allocates computational resources to the offloaded tasks.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, the performance of the proposed mechanism is evaluated through numerical simulations designed by using the MATLAB. e compared algorithms are the competitionbased algorithm [30] and the user-satisfaction-based offloading algorithm [31]. eir features are described as follows:…”
Section: Simulation and Analysismentioning
confidence: 99%
“…In addition, the parameters of the other three mobile devices include CPU processing parameters, such as χ i , α i , and β i . ese parameters are adopted as in [30]. In the simulation, the type of the mobile device in the mobile-edge cloud computing scenario is randomly selected among the abovementioned three types, and each mobile device has only one task waiting to be executed.…”
Section: Simulation Setupmentioning
confidence: 99%
“…A few recent works provided a game theoretic treatment of the mobile computation offloading problem for a single time slot [31], [32], [5], [18], [33], [34], [7]. [31] considers a two-stage game, where first each mobile user chooses the parts of its task to offload, and then the cloud allocates computational resources to the offloaded parts.…”
Section: R E L At E D W O R Kmentioning
confidence: 99%
“…[32] considered a three-tier cloud architecture, and provided a distributed algorithm for the computing a mixed strategy equilibrium. [33] considered tasks that arrive simultaneously and a single wireless link, and showed the existence of equilibria when all mobile users have the same delay budget. [5] showed that assuming a single wireless link and link rates determined by the Shannon capacity of an interference channel, the resulting game is a potential game.…”
Section: R E L At E D W O R Kmentioning
confidence: 99%